The role of RNA methyltransferase METTL3 in gynecologic cancers: Results and mechanisms - Zhang, Yuxiang; Zhang, Na (Frontiers in Pharmacology, 2023)
N6-methyladenosine (m6A) methylation is the most prevalent mRNA modification in eukaryotes, and it is defined as the methylation of nitrogen atoms on the six adenine (A) bases of RNA in the presence of methyltransferases. Being one of the components of m6A methyltransferase, methyltransferase-like 3 (Mettl3) plays a decisive catalytic role in the whole process of m6A methylation. Recent studies have confirmed that, in gynecologic tumors, m6A is associated with a broad spectrum of biological processes and it significantly affects tumor progression and patient prognosis, in which the role of Mettl3 cannot be ignored. Mettl3 is involved in numerous pathophysiological functions, such as embryonic development, fat accumulation, and tumor progression. Moreover, Mettl3 may serve as a potential target for treating gynecologic malignancies, thus, benefiting patients and prolonging survival. However, the role and mechanism of Mettl3 in gynecologic malignancies need to be studied further. This paper reviews the recent progression on Mettl3 in gynecologic malignancies, hoping to provide a reference for further research.